Pembangunan Rubrik Pentaksiran Amali Bagi Kursus Kawalan Motor Program Teknologi Elektrik Di Kolej Vokasional - MAZNI FAIZAL, NURUL HUSNA (Research and Innovation in Technical and Vocational Education and Training, 2023)
This study was conducted to develop assessment rubric for Motor Control course of Electrical Technology program for Vocational College. The rubric was created using the rubric development method proposed by Steven and Levi consist of four processes which are reflecting, listing, grouping and labelling and application. Interview with three experts and document analysis were used to determine the criteria and descriptors of rubric. Overall, there are three basic components, and 18 criteria were developed in the rubric. The main criteria are work process, product, and value. Overall, the developed rubric satisfies the criteria for assessing student achievement.